‘“By whom shall she arise? For she is small”: the Wales-Israel tradition in the Edwardian period - Jasmine Donahaye (The Jew in Late-Victorian and Edwardian Culture: Between the East End and East Africa, 2009)
This chapter analyses the relationship of purported Welsh identification with Jews to Welsh national models, analysing work by Dorian Llywelyn, Willian Rubinstein, Lily Tobias and others.